Digital transformation of warehouse management through web-based information system at CV. Al Salam - Janah, Selvi Miftakhul; Atina, Vihi; Permatasari, Hanifah (Institute of Computer Science (IOCS), 2024)
Effective and efficient inventory management is crucial for the operational success of trading companies. CV. Al Salam, engaged in fabric trading in Sukoharjo, faces significant challenges in managing fabric stocks at their main warehouse. Currently, inventory management at CV. Al Salam is done manually, often leading to issues such as recording errors and document piles. This research aims to develop a web-based warehouse information system using technologies like PHP, MySQL, and JavaScript to address these challenges. The system is expected to provide real-time stock monitoring, automated restock notifications, and an interactive dashboard for data analysis. The Waterfall development method is employed, covering requirements analysis, design, development, and testing phases. Testing results show the system functions according to specifications with a 100% success rate, enhancing recording accuracy and speeding up reporting and goods distribution processes. The research findings indicate that this system successfully improves operational efficiency at CV. Al Salam by reducing recording errors and accelerating the reporting and distribution processes.